Turkey's Involvement in the Syrian Conflict from a Defense Management Perspective - Muhammad Zulham; Hendra Maujana Saragih; Suyono Thamrin; Tatar Bonar Silitonga (AJIS: Academic Journal of Islamic Studies, 2020)
This article will discuss Turkey's interests in resolving the Syrian conflict from the perspective of defense management. The Syrian conflict that demanded the resignation of President Bashar al-Assad made all countries in the world want to participate in conflict resolution. Turkey is no exception. Turkey is one of Syria’s close neighbors and is interested in it. National defense and economic interests are the main factors of Turkey in the Syrian conflict. The deployment of strategic depth of foreign policy has become the benchmark for conflict resolution. National defense management is a new science for realizing national interests, and its strategic environment must be reviewed. Therefore, as one of the important actors in the Middle East, Turkey has the aforementioned policies in realizing its national interests. This article uses qualitative methods in the conclusion. This article uses assumptions from realism to constructivism, national interest theory of national defense theory and national defense management theory. The conclusion of this article is that defense management (Assad's call for resignation) is based on preventing Syrian refugees from going to Turkey. A large number of refugees from Syria may undermine Turkey's security and stability. The aim is to maintain Turkey’s social and economic stability, which may be shaken by the existence of these refugee groups. Achieving this goal by providing support and weapon assistance to the Syrian rebels is considered a form of preventing the spread of the Syrian conflict. In addition, Turkey also hopes to join NATO